ANALISIS CERITA PENDEK KARYA SISWA KELAS IX SMP NEGERI 5 PONTIANAK TAHUN PELAJARAN 2019/2020 - Alpina Sari; Nanang Heryana; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstrakThis research was motivated by the researcher's interest in short stories made by grade IX students of junior high school. The main reason for the researcher, to find how the IX grade students express their emotions, and explore their creativity in critical thinking and produce good stories. The researcher hopes can help students develop their interest and creativity in writing. This study focuses on the structure, language, and building blocks of short stories. The research method used is descriptive with a quantitative design. The research data is form of analysis tables, the source of data is the short stories of class IX students, and the research tool is researcher as the main instrument. The results of this study indicate that the students' ability in writing short stories is quite good, but it must be more improved on existing theories. Students are advised always be guided so that they are directed.Keywords: Analysis, Student Work, Short Story